Knowledge Management, Innovation, and Islamic Banking - Lia Amaliawiati; Aam (SMART Insight, 2022)
The external environment in which the company as an open system operates is constantly increasing dynamically. Companies accustomed to formulating their business strategies by predicting trends in the next five to ten years are frustrated because changes occur quickly and cannot be expected. As companies continue to emerge that are primarily engaged in the banking business and Islamic banking, the competitive competition between one company and another is increasing. This competition is one of the challenges and obstacles the company faces. To overcome this, one way that can be used to be superior to other companies is to make the best use of the information contained within the company, which can be used to meet the company's information needs. In the course of their business, companies will face significant employee turnover. In addition, the knowledge possessed by one employee becomes an asset of the employee himself. This is an obstacle. If the employee who has this knowledge is not in the office or out of the company, the knowledge will go along with the owner. As a result, the cost and time that the company must spend to provide training to new employees are more detrimental to the company. The concept of science that can answer these challenges is Knowledge Management. This study aims to determine the development of Knowledge Management in Islamic Banks research trends published by reputable scopus publication. The data analyzed consisted of 84 indexed research publications. The data is then processed and analyzed using the VoS viewer application to find out the bibliometric map of the development of Knowledge Management in Islamic Bank research.